2021
DOI: 10.1186/s12868-021-00616-5
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral sensitization induced by methamphetamine causes differential alterations in gene expression and histone acetylation of the prefrontal cortex in rats

Abstract: Background Methamphetamine (METH) is one of the most widely abused illicit substances worldwide; unfortunately, its addiction mechanism remains unclear. Based on accumulating evidence, changes in gene expression and chromatin modifications might be related to the persistent effects of METH on the brain. In the present study, we took advantage of METH-induced behavioral sensitization as an animal model that reflects some aspects of drug addiction and examined the changes in gene expression and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…These results support the notion that enrichment at gene promoters is not directly related to the levels of the histone protein under investigation. A recent ChIP-chip analysis using a rat model of METH-induced behavioral sensitization discovered increased H3 acetylation in a large number of gene promoters (241 genes) and increased H4 acetylation in a fewer number of gene promoters (10 genes) in the pCTX [65]. Interestingly, H4 hyperacetylation was found to contribute to increased expression of Angp32a, a gene is involved in the regulation of synaptic plasticity and memory [65].…”
Section: Chronic Effects Of Meth On Histone Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results support the notion that enrichment at gene promoters is not directly related to the levels of the histone protein under investigation. A recent ChIP-chip analysis using a rat model of METH-induced behavioral sensitization discovered increased H3 acetylation in a large number of gene promoters (241 genes) and increased H4 acetylation in a fewer number of gene promoters (10 genes) in the pCTX [65]. Interestingly, H4 hyperacetylation was found to contribute to increased expression of Angp32a, a gene is involved in the regulation of synaptic plasticity and memory [65].…”
Section: Chronic Effects Of Meth On Histone Acetylationmentioning
confidence: 99%
“…METH use is known to be accompanied with behavioral sensitization that can last for several weeks to months in rodents [65,70]. Interestingly, the class I HDACi, valproic acid (VPA), can attenuate behavioral sensitization responses [71].…”
Section: Role Of Hdac Inhibitors In Meth Exposurementioning
confidence: 99%
“…Consistent with previous studies, we found that METH F1 , which is insufficient to induce CPP in naïve mice, effectively induced METH-preferred behaviors in METH-sired male F1 and not in SAL-sired male F1, indicating an enhanced sensitivities to drugs in F1 of sires exposed to METH. The mPFC has been implicated in the vulnerability to drug abuse [6][7][8]. Currently, little literature uncover the association of paternal METH intake with offspring mPFC alteration.…”
Section: Discussionmentioning
confidence: 99%
“…The medial prefrontal cortex (mPFC) is critically implicated in the processes of METH addiction [4, 5] and susceptibility to drugs [68]. Human imaging studies show that prenatal METH exposure significantly affect the volume, cortical thickness and connection of offspring brains, especially the prefrontal cortex (PFC) [7, 9, 10]. Previously, we found that mPFC were blunted to stimulants in METH-sired mice during adulthood [11].…”
Section: Introductionmentioning
confidence: 99%
“…Methamphetamine (MA) is synthesized on the basis of ephedrine, which has the effect of mental stimulation ( Chen et al, 2021 ). MA is one of the most widely abused illegal substances in the world, but unfortunately, there are still very few studies on detoxification after a period of time ( Huang et al, 2021 ; Li et al, 2021 ). Due to the high addiction, it is prohibited in many countries.…”
Section: Introductionmentioning
confidence: 99%